Beating the human rights drum: Applying human rights standards to NGOs' governance - Maria Nassali (Pretoria University Law Press (PULP), 2015)
About the publication The main contention of this book is that non-governmental organisations (NGOs) have the obligation to empower themselves internally before they can champion the empowerment of others. This entails being knowledgeable in the area of work; forging linkages with broader civil society and academia; building on the positive cultural values that resonate with human rights to stimulate mass support; and balancing the different accountabilities to the law, boards, membership, self-regulatory mechanisms, public and donors. This book is based on the author's (LLD) thesis, submitted to the University of Pretoria. The thesis was subsequently revised, based on a further peer-review process. About the editor: Maria Nassali is Chief Executive Officer of International Governance Alliance (iGA). School of Law, Makerere University, Uganda Table of Contents Foreword Preface Acknowledgments About the author Dedication Cases, statutes and documents Acronyms Conceptualising the role of NGOs in the human rights movement 1 Introduction and overview 2 The concealed and unchecked power of NGOs: A background discussion 3 Linking rights, governance and development 4 Book overview The human rights obligations of NGOs in the international arena 1 Introduction 2 NGOs' obligations under international law 2.1 NGOs do not have legal obligations under international human rights law 2.2 NGOs legal obligations to respect and promote human rights 3 The rights-based approach as an instrument of good governance 4 Implications of the rights-based approach to NGO governance 4.1 Express linkage to human rights 4.2 Accountability and Transparency 4.3 Participation and inclusion 4.4 Equity, non-discrimination and empowerment 5 Conclusion NGOs and the principle of express linkage to human rights 1 Introduction 2 Why all NGOs should apply human right principles to their governance and management 3 The principle of express linkage to rights and the universality of human rights 3.1 The universality of rights: The conceptualisation of rights amongst NNGOs and SNGOs 3.2 The universality of rights: African NGOs and cultural interpretation 4 The principle of indivisibility of rights: A case study of DNGOS and HURINGOs 4.1 The traditional relationship between DNGOs and HURINGOs 4.2 The indivisibility of rights: HURINGOs and the development agenda 5 Conclusion NGOs and the principle of accountability 1 Introduction 2 Accountability through the law 2.1 The right to exist informally as an organisation 2.2 The right to legal existence and the obligation to register 2.3 Protection from unwarranted state interference 3 Accountability to the sector wide mechanism for self-regulation 4 Accountability to the NGO Board 4.1 The Board as a source of accountability 4.2 The mechanisms of accountability by the Board 4 Accountability to members 5 Accountability to the communities 6 Transparency and public accountability 7 Accountability to donors 8 Conclusion NGOs and the principles of participation and inclusion 1 Introduction 2 Founders and inclusive and participatory management 3 Broadening participation through transitions and succession 4 Participation and the management of conflicts 5 NGOs and community participation 6 Peer NGO networks and coalitions 7 Participation of NGOs in political society 7.1 Making the case for NGO's political participation 7.2 Collaboration and critical engagement with government 7.3 Civil disobedience 7.4 Entering the state 8 NGOs and the African Commission on Human and Peoples' Rights 9 NGO participation with National Human Rights Institutions (NHRIs) 10 Conclusion Exploring the principles of empowerment, equity and non-discrimination 1 Introduction 2 NGOs, empowerment and human rights and governance expertise 2.1 NGOs and human rights and governance expertise 2.2 The dilemmas of volunteerism and the payment of competitive remuneration 2.3 Empowerment and sustaining activism 3 Empowerment and resource mobilisation to achieve an NGO's mission 3.1 NGOs and government funding 3.2 NGOs and foreign donor funding 4 Empowerment of marginalised groups within the NGO sector 4.1 NGOs and the empowerment of women 4.2 NGOs and the empowerment of the youth 4.3 NGOs and sexual minorities 4.4 NGOs and the empowerment of racial and ethnic minorities 5 The contemporary efforts of promoting equality and empowerment within the NNGOs/ SNGO relationship 6 Conclusion Walking the talk: Holding NGOs accountable to human rights principles 1 Introduction 2 NGOs' human rights obligations 3 NGOs' human rights obligations elaborated 3.1 The principle of express linkage to rights (mainstreaming) 3.2 The principles of accountability and transparency 3.3 The principle of participation and inclusion 3.4 The principles of equity, non-discrimination and empowerment 4 Status of NGOs' observance of human rights obligations in Kenya, Tanzania, Uganda and South Africa 4.1 The status of observance of the principle of linkage to rights 4.2 The status of observance of the principles of accountability and transparency 4.3 The status of observance of the principles of participation and inclusion 4.4 The status of observance of the principles of equity, non-discrimination and empowerment 5 Recommendations 5.1 NGO obligations under the principles of linkage to rights 5.2 NGO obligations under the principles of accountability and transparency 5.3 NGO obligations under the principles of participation and inclusion 5.4 Equity, Non-discrimination and Empowerment 6 Concluding thoughts Bibliography